The Problem of the Production of Deposition of Testimony during the Disclosure and Investigation of Crimes Related to Trafficking in Narcotic Drugs and Psychotropic Substances - ZHARMAGAMBETOVA, Dinar A.; BERISTEMOVA, Raukhan G.; BEGALIYEV, Bakhytbek A.; BEGALIYEV, Yernar N. (Journal of Advanced Research in Law and Economics, 2019)
The topic of the article is relevant because practical experience in pre-trial investigation of criminal offenses related to illicit drug trafficking that affect the morality and health of the population of Kazakhstan shows a serious problem related to the activities of state bodies in counteracting this phenomenon. This article deals with the problems of conducting the deposition of witness testimony on materials of pre-trial investigations in the sphere of illicit drug trafficking and precursors. Analyzed the practical activities of pre-trial investigation in the investigation of criminal offenses in this category. The authors propose a mechanism to simplify procedures for the recognition of narcotic drugs and psychotropic substances as such, through the introduction of an integrated registry of the National Assembly (narcotic drugs) and PV (psychotropic substances), with an active (daily) solved update, formed on the basis of expert opinions. Options have been proposed for eliminating gaps in the conduct of the deposit by the investigating judge, as well as in investigating crimes.